Faktor-Faktor Yang Berpengaruh Terhadap Kinerja Keuangan - Alvon Kertorahardjo, Liana Susanto (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to examine the effect of institutional ownership, solvability, liquidity, and firm size on financial performance. This study uses secondary data which was tested using eviews program 11.0. Samples that have been selected by purposive sampling method and selected as many as 73 manufacture companies as a sample from 185 companies that go public listed on the IDX for the period 2016 - 2018. The results of the research on solvability have significantly positive, and the other variables (institutional ownership, liquidity, and firm size) are not significant to the financial performance.